Cassava peel as adsorbent for Rhodamine B dye removal of Rhodamine B Dye - Murugeson Pillai, Priyadharsheniy (2018)
Agricultural waste which is also known as residues left from agriculture sector such as fruit peels, coconut husk and maize cob are used in treating wastewater, most commonly in textile industries to remove dyes. The best method that can be used in order to treat the wastewater and to remove the dye is adsorption. Adsorption method is most preferable based on cost, time and efficiency. This study was carried out to investigate the potential of Cassava peel as an adsorbent for the removal of Rhodamine B dye in waste water treatment. The maximum percentage of Rhodamine B dye removal was 98.47% at the optimized condition (adsorbent size = 0.125 mm, adsorbent dosage = 5.0 g, initial dye concentration = 300 mg/L, contact time = 24 hours and pH = 2). Langmuir and Freundlich isotherm models were used to investigate the adsorption favourability. Results showed that the equilibrium data was best fitted to Langmuir adsorption isotherm model with correlation coefficient R2 = 1, which is monolayer adsorption. The maximum adsorption capacity was 8.55 mg/g. The results of this study shows that the agricultural waste, Cassava peel has the ability to act as an adsorbent for the removal of Rhodamine B dye in waste water treatment.